Electrochemical evaluation of ion substituted-hydroxyapatite on HeLa cells plasma membrane potential. Issue 1 (1st January 2019) - Asimeng, Bernard Owusu; Tiburu, Elvis Kwason; Effah Kaufmann, Elsie; Paemka, Lily; Hayford, Claude Fiifi; Essien-Baidoo, Samuel; Dzikunu, Obed Korshie; Anani, Prince Atsu
Abstract: This study reports the electrochemical activities of a novel ion substituted-Hydroxyapatite (HAp) material in contact with HeLa cells. The work was performed to evaluate the inhibitory effects of various concentrations of HAp on ion transfer mechanisms in HeLa cells. The materials (n = 2: HAp1 and HAp3) were prepared at different stirring times from Achatina achatina snail shells and phosphate-containing solution. The structure of the materials and the trace elements concentration were evaluated using x-ray diffractometry and infrared spectrometry as well as atomic absorption spectroscopy. Electrochemical studies conducted on the cells after 30 min of exposure to the materials demonstrated different responses as elucidated by cyclic voltammetry. The voltammograms revealed HAp1 to be non-redox whereas HAp3 was redox active. Minimal concentrations of HAp1 showed high anodic peak current when compared to the HeLa cells alone, indicating a hyperpolarization of the cells. The peak current gradually reduced as the concentration of HAp1 was increased, and then followed by a sudden rise suggesting inhibition of the cell action potential. HAp3 showed a wavy pattern of the anodic peak current when the material concentration was varied. Peak currents of 0.92 ± 0.03 nA and 0.57 ± 0.01 nA were recorded for HAp1 and HAp3, respectively at the highest concentration of 5 µ L. The results suggest that different inhibitory mechanisms are at play on the voltage-gated ion channels of the cells, indicating the possibility of using the materials to achieve different cancer proliferation inhibition.